Assessment of Thermo Modernization Using the Global Cost Method. (November 2015) - Basinska, Malgorzata; Koczyk, Halina; Kosmowski, Andrzej
Abstract: The article uses the global costs method to choose the best thermo modernization solutions for the buildings. Global costs were calculated according to the cost-optimal draft regulation as summing up the initial investment costs and the discounted annual operating costs. Requirements of thermo modernization work assumed to comply with the new requirements of the building's thermal protection entered in Poland on January 1, 2014. The case study was carried out for multi-family building located in Poznan. Global cost method was compared with the more common indicators of economic evaluation Simple Pay Back Time (SPBT), and Net Present Value (NPV).